PERANCANGAN BUKU FOTOGRAFI NAMA-NAMA HEWAN TERNAK DENGAN SISTEM ISYARAT BAHASA INDONESIA (SIBI) SEBAGAI MEDIA PEMBELAJARAN ANAK TUNARUNGU DI TKLB-B KARYA MULIA SURABAYA - Rivan, Didit; Riyanto, Darwin Yuwono; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
The purpose of this study was to design Photography Books Animal Names With Indonesian Broadcasting System ( SIBI ) For Deaf Children Learning Media in TKLB - B Karya Mulia Surabaya . Education is now very much forward to the next generation , just to note again is the children who have physical limitations . They need to be learning and understanding more through special books especially for children with hearing impairment. Textbooks should be developed using Indonesian sign language system . Keyword : Book Illustration , Design , SIBI , Livestock , Children .